2017
DOI: 10.1016/j.msec.2017.03.267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of telopeptides on the structural and physical properties of polymeric and monomeric acid-soluble type I collagen

Abstract: Currently two factors hinder the use of collagen as building block of regenerative devices: the limited mechanical strength in aqueous environment, and potential antigenicity. Polymeric collagen is naturally found in the cross-linked state and is mechanically tougher than the monomeric, acid-soluble collagen ex vivo. The antigenicity of collagen, on the other hand, is mainly ascribed to inter-species variations in amino acid sequences of the non-helical terminal telopeptides. These telopeptides can be removed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 31 publications
2
42
0
1
Order By: Relevance
“…Both sol-gel and hydrogel transition temperatures then affected the collagen fibril networks as macroscopic changes. The thermal properties of collagen materials were already reported by other groups [11][12][13][17][18][19]. Although the denaturation temperature was dependent in the sample conditions such as the water content, our results are not inconsistent with previous reports.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Both sol-gel and hydrogel transition temperatures then affected the collagen fibril networks as macroscopic changes. The thermal properties of collagen materials were already reported by other groups [11][12][13][17][18][19]. Although the denaturation temperature was dependent in the sample conditions such as the water content, our results are not inconsistent with previous reports.…”
Section: Discussionsupporting
confidence: 76%
“…Acid-extracted collagens maintain the telopeptide regions, but enzyme-treated collagens do not. It is reported that the telopeptide affects the crosslinking as well as the immunogenicity of the collagen [13,14]. Therefore, the physicochemical properties of collagen materials largely depend on the collagen origin and the collagen preparation procedures [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…telopeptides, with up to half of the amino acid residues in these regions exhibiting interspecies variation. Telopeptide-free collagen, also called atelocollagen, can be obtained via pepsin-induced extraction [31], whose yield is reported to be higher compared to acidic extraction [32]. The introduction of pepsin in the extraction medium allows for the selective cleavage of peptide bonds located in the terminal non-helical regions, potentially reducing collagen antigenicity.…”
Section: Collagen Sources and Antigenicitymentioning
confidence: 99%
“…However, the degradation of collagen produces hydrolyzed collagen (HC), which consists of segmented proteins with low molecular weight (Mw) between 1 kDa and 10 kDa [16]. HC is obtained by denaturation of native collagen followed by an enzymatic process that breaks down the protein chains into small peptides cleaving the protein at specific amide bonds [17][18][19]. The use of natural peptides like collagen hydrolysates has been widely utilized due to their excellent biocompatibility, easy biodegradability, and weak antigenicity [20].…”
Section: Introductionmentioning
confidence: 99%